Association between postoperative bulla neogenesis at the staple line and resected lung weight for primary spontaneous pneumothorax: a retrospective study using the inverse-probability of treatment weighted method in patients grouped according to age - Tsuboshima, Kenji; Nagata, Machiko; Wakahara, Teppei; Matoba, Yasumi; Maniwa, Yoshimasa (Journal of Thoracic Disease, 2016)
Background: Bullectomy using autosutures is the standard procedure in patients with primary spontaneous pneumothorax (PSP). However, postoperative bulla neogenesis (POBN) along the staple line is relatively common and promotes PSP recurrence. We have previously reported the relationship between POBN and resected lung weight (LW). However, recently published data indicate that young patients with PSP have a high postoperative recurrence rate. Therefore, we evaluated the relationship between POBN and LW in PSP patients, subdivided according to age. Methods: Between February 2011 and April 2016, 96 lung-resection sites in 67 patients who underwent bullectomy were evaluated. Patients were subdivided into two groups by age: Y group (